Asymptomatic CMV infections in long-term renal transplant recipients are associated with the loss of FcRγ from LIR-1+ NK cells - Makwana, N.; Foley, B.; Lee, S.; Fernandez, S.; Irish, A.; Price, Patricia (Wiley-VCH Verlag GmbH & Co. KGaA, 2016)
While it is established that cytomegalovirus (CMV) disease affects NK-cell profiles, the functional consequences of asymptomatic CMV replication are unclear. Here, we characterize NK cells in clinically stable renal transplant recipients (RTRs; n = 48) >2 years after transplantation. RTRs and age-matched controls (n = 32) were stratified by their CMV serostatus and the presence of measurable CMV DNA. CMV antibody or CMV DNA influenced expression of NKG2C, LIR-1, NKp30, NKp46, and FcRγ, a signaling adaptor molecule, on CD56dim NK cells. Phenotypic changes ascribed to CMV were clearer in RTRs than in control subjects and affected NK-cell function as assessed by TNF-α and CD107a expression. The most active NK cells were FcRγ–LIR-1+NKG2C– and displayed high antibody-dependent cell cytotoxicity responses in the presence of immobilized CMV glycoprotein B reactive antibody. However, perforin levels in supernatants from RTRs with active CMV replication were low. Overall we demonstrate that CMV can be reactivated in symptom-free renal transplant recipients, affecting the phenotypic, and functional profiles of NK cells. Continuous exposure to CMV may maintain and expand NK cells that lack FcRγ but express LIR-1.